PERANCANGAN GAME EDUKASI “THE KNIGHT OF PANDEMIC” DENGAN MENGGUNAKAN MODEL GAME DEVELOPMENT LIFE CYCLE (GDLC) - Pandu Dewonoto Laut Santoso; Nurjaya (CV. Multi Kreasi Media, 2023)
Educational games are part of a variety of game genres whose implementation is intended as a medium for exposing various types of material in an interactive and attractive manner by and for a group of people. The game development model implemented in this study is the Game Development Life Cycle (GDLC) model which consists of 6 phases, namely initiation, pre-production, testing, beta and release, while some of the advantages of the GDLC model include the needs and goals of game development can be clearly defined at the initiation stage, concept maturation and development of game assets can be carried out optimally at the pre-production stage, as well as testing which is carried out in stages involving both the developer and the user. The main problem in this research is the decrease in public awareness and interest in the pandemic situation caused by the application of Covid-19 pandemic educational media that is monotonous, less attractive and less interactive, while the main objective of conducting this research is to design and develop Covid-19 pandemic educational media. in the form of games are interactive and attractive. Based on the research that has been carried out, the final results are obtained which illustrate that the pandemic educational game designed and developed in this study is interactive and attractive so that it can play an active role in increasing public awareness and interest regarding various matters related to the Covid-19 pandemic situation.